Polyfunctional Fc Dependent Activity of Antibodies to Native Trimeric Envelope in HIV Elite Controllers - Kant, Sanket; Zhang, Ningyu; Barbé, Alexandre; Routy, Jean-Pierre; Tremblay, Cécile; Thomas, Réjean; Szabo, Jason; Côté, Pierre; Trottier, Benoit; LeBlanc, Roger; Rouleau, Danielle; Harris, Marianne; et al. (Frontiers in Immunology, 2020)
Antibody dependent (AD) functions such as AD cellular cytotoxicity (ADCC) were associated with lower viral load (VL) in untreated HIV progressors and protection from HIV infection in the modestly protective RV144 HIV vaccine trial. Target cells used to measure ADCC, AD complement deposition (ADCD) and AD cellular trogocytosis (ADCT) have been either HIV envelope (Env) gp120-coated CEM.NKr.CCR5 cells or HIV infected cell cultures. In HIV infected cell cultures, uninfected bystander cells take up gp120 shed from infected cells. Both gp120-coated and gp120+ bystander cells expose CD4 induced (CD4i) epitopes, which are normally hidden in native trimeric Env expressed by genuinely HIV infected cells since Nef and Vpu downmodulate cell surface CD4. AD assays using either of these target cells probe for CD4i Abs that are abundant in HIV+ plasma but that do not recognize HIV-infected cells. Here, we examined ADCC, ADCD and ADCT functions using a target cell line, siCEM cells, whose HIV infection frequency nears 100% and that expresses HIV Env in a native trimeric closed conformation. Using siCEM cells as targets, we probed the binding and AD functions of anti-gp120/Env Abs in plasma from HIV-infected untreated progressor (UTP, n=18) and treated (TP, n=24) subjects, compared to that in Elite Controllers (EC, n=37) and Viral Controllers (VC, n=16), which are rare subsets of HIV-infected individuals who maintain undetectable or low VL, respectively, without treatment. Gp120-coated beads were used to measure AD cellular phagocytosis (ADCP). Equivalent concentrations of input IgG in plasma from UTPs, ECs, and VCs supported higher levels of all AD functions tested than plasma from TPs. When AD activities were normalized to the concentration of anti-gp120/Env-specific Abs, between-group differences largely disappeared. This finding suggests that the anti-gp120/Env Abs concentrations and not their potency determined AD functional levels in these assays. ECs did differ from the other groups by having AD functions that were highly polyfunctional and highly correlated with each other. PCR measurement of HIV reservoir size showed that ADCC activity was higher in ECs and VCs with a reservoir size below the limit of detection compared to those having a measurable HIV reservoir size.